2009
DOI: 10.4081/1182
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphology and immunohistochemical localization of the gonadotropin-releasing hormone in the bluefin tuna, Thunnus thynnus

Abstract: The present study was focused on the morphology of the diencephalic nuclei (likely involved in reproductive functions) as well as on the distribution of GnRH (gonadotropin-releasing hormone) in the rhinencephalon, telencephalon and the diencephalon of the brain of bluefin tuna (Thunnus thynnus) by means of immunohistochemistry. Bluefin tuna has an encephalization quotient (QE) similar to that of other large pelagic fish. Its brain exhibits well-developed optic tecta and corpus cerebelli. The diencephalic neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Three types of neuronal cells, including large, medium and small-sized neurons, were sbGnRH-positive in the immunohistochemistry and immunofluorescence assay (Figs 4 and 5), indicating that these cells are involved in the production of the sbGnRH-like peptide in this fish. Several previous works also showed the occurrence of sbGnRH-ir neuronal cells in the preopticus-periventricularis nucleus of the brain in other fish species: Thunnus thynnus (Palmieri et al 2008), Paralichthys olivaceus (Pham et al 2007) and Scomber japonicus (Selvaraj et al 2009). However, these studies did not identify the neuronal types, so this is the first report that has shown that the large, medium and small-sized neurons in the preopticus-periventricularis nucleus can produce the GnRH-like peptide.…”
Section: Discussionmentioning
confidence: 75%
“…Three types of neuronal cells, including large, medium and small-sized neurons, were sbGnRH-positive in the immunohistochemistry and immunofluorescence assay (Figs 4 and 5), indicating that these cells are involved in the production of the sbGnRH-like peptide in this fish. Several previous works also showed the occurrence of sbGnRH-ir neuronal cells in the preopticus-periventricularis nucleus of the brain in other fish species: Thunnus thynnus (Palmieri et al 2008), Paralichthys olivaceus (Pham et al 2007) and Scomber japonicus (Selvaraj et al 2009). However, these studies did not identify the neuronal types, so this is the first report that has shown that the large, medium and small-sized neurons in the preopticus-periventricularis nucleus can produce the GnRH-like peptide.…”
Section: Discussionmentioning
confidence: 75%
“…These results indicate that GnRH2 does not regulate GTH secretion directly, but GnRH2 can be a neuromodulator and influence GTH in other ways. Although GnRH2-ir cell bodies were detected in the dorsal part of the PO as in the case of bluefin tuna Thunnus thynnus (Palmieri et al, 2008), gnrh2-expressing neurons were not detected in this region by in situ hybridization. Because the localization of GnRH1-ir cell bodies and that of GnRH2-ir cell bodies in the PO were different, and GnRH3-ir cell bodies were not detected in the PO, the GnRH2-ir cell bodies detected in the dorsal part of the PO were not the result of a cross-reaction between GnRH1 and GnRH3.…”
Section: Discussionmentioning
confidence: 85%
“…A previous observation showed that all populations were positively reacted with anti-GnRH-like peptide antibody in R. brachysoma (Senarat et al, 2019), and at present it is unclear how the functions of these three neuronal populations are different. Since these three nuclei are important regions for GnRH production in R. brachysoma (Senarat et al, 2019) as well as other fishes (Peter et al, 1991;Palmieri et al, 2008), further investigation on these three types of neurons are required.…”
Section: Resultsmentioning
confidence: 99%